2019
DOI: 10.1017/inp.2019.29
|View full text |Cite
|
Sign up to set email alerts
|

Selective herbicides for control of hen’s eyes (Ardisia crenata) in forests and natural areas

Abstract: Hen’s eyes (Ardisia crenata Sims) is a shade-tolerant invasive shrub displacing native understory in forests of the Coastal Plain of the southeastern United States. Few studies have explored herbicide effectiveness on A. crenata, with foliar applications of triclopyr amine or triclopyr ester typically referenced as the standard treatments. This study evaluated efficacy of eight foliar herbicide treatments and a nontreated check at three locations at 12 mo after the first treatment (12MAT1) and 12 mo after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Greenhouse studies by Dias et al (2017) found that the new formulations of triclopyr exhibit similar activity on common crop species. However, field studies using the new formulations revealed that there may be some variability depending on the target species, as the acid formulation was very effective at controlling hen's eyes ( Ardisia crenata Sims), but the choline formulation did not result in significant control of this species (Cristan et al 2019). Mechanisms for this have not been well studied, especially for the acid and choline formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse studies by Dias et al (2017) found that the new formulations of triclopyr exhibit similar activity on common crop species. However, field studies using the new formulations revealed that there may be some variability depending on the target species, as the acid formulation was very effective at controlling hen's eyes ( Ardisia crenata Sims), but the choline formulation did not result in significant control of this species (Cristan et al 2019). Mechanisms for this have not been well studied, especially for the acid and choline formulations.…”
Section: Introductionmentioning
confidence: 99%
“…(Ramsey et al 2012) and MSO is recommended for titi applications, but we found no research supporting its use for woody plants. Triclopyr is the most lipophilic among these herbicides (Shaner 2014) and is commonly used for titi control or other waxy leaf shrubs in the region (Cristan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a relatively new acid formulation of triclopyr has been shown to be comparable to and better than the triclopyr amine formulation on Tahitian bridal veil [ Gibasis pellucida (M. Martens & Galeotti) D.R. Hunt] (Yu et al 2022) and hen’s eyes ( Ardisia crenata Sims) (Cristan et al 2019), respectively. The triclopyr acid formulation warrants additional testing, as it is labeled for aquatic use and, operationally, has been shown to be effective at lower use rates than current rates recommended for triclopyr ester for basal bark treatment of S. terebinthifolia (Bell 2019).…”
Section: Introductionmentioning
confidence: 99%